Efectuate: (3x+4)la a 2 +5(x—3) la a 2 —4x(x+3)
Raspunsul?
Răspunsuri la întrebare
Răspuns de
1
( 3x + 4 )² + 5 ( x - 3 )² - 4x (x+3 ) = folosim formula (a+b)² = a²+2ab+b², deci:
= 9x² +2·3x·4 + 16 + 5( x²-2x·3+9) - 4x² - 12x =
= 9x² + 24x + 16 + 5x² - 30x + 45 - 4x² - 12x =
=10x² -18x + 61
= 9x² +2·3x·4 + 16 + 5( x²-2x·3+9) - 4x² - 12x =
= 9x² + 24x + 16 + 5x² - 30x + 45 - 4x² - 12x =
=10x² -18x + 61
Alte întrebări interesante
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
10 ani în urmă
Chimie,
10 ani în urmă
Matematică,
10 ani în urmă